Splenic artery embolization for the management of severe life-threatening warm autoimmune hemolytic anemia - Aya Egbaria; Naiel Bisharat (Hematology)
Background Urgent splenectomy is recommended for the management of highly transfusion-dependent life-threatening warm autoimmune hemolytic anemia, while for individuals unfit for surgery, splenic embolization is an alternative treatment option. However, reports on its use in this context are sparse, and data on patient outcomes, effectiveness, and safety remain limited.Case presentation A 21-year-old female patient presented with severe transfusion-dependent, life-threatening, warm autoimmune hemolytic anemia that was unresponsive to steroids and rituximab, reaching a nadir of 2.3 g/dL. Due to the severity of the anemia, she was unfit for surgery and therefore she underwent embolization of the lower two-thirds of the spleen parenchyma. Within 24 h after embolization, her hemoglobin level increased to 4.9 g/dL. A literature search yielded eight other reports describing the use of splenic embolization in severe warm autoimmune hemolytic anemia. No procedure-related deaths were reported. While some complications may require invasive interventions (e.g. splenic abscess drainage, splenectomy), the improvement in blood counts following splenic embolization often facilitated safer conditions for these procedures.Conclusion Based on this report and review of the literature, the use of splenic embolization in cases of transfusion-dependent, life-threatening, warm autoimmune hemolytic anemia is safe and is associated with marked improvement in hemoglobin levels.